Antitubercular activities of Crinum asiaticum bulb extract using aeroso-linduced Mycobacterium smegmatis in mice model - Michael Ofori, Cynthia Amaning Danquah, Paul Poku Sampene Ossei, Gilbrene Rahamani,, Isaac Newton Nugbemado, Peace Doe, Theophilus Kwesi Ninkyi (Journal of Applied Pharmaceutical Science, 2022)
Tuberculosis (TB) is one of the highly infectious diseases affecting one-third of the world’s population. The emergence of multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant (XDR) strains of Mycobacterium tuberculosis has affected TB management. The death toll from MDR- and XDR-TB is estimated to be more than a million people each year which is alarming; therefore, there is a need to discover novel compounds which could be developed to tackle resistant TB. The extracts from the bulbs of the plant Crinum asiaticum are used ethnomedicinally to treat upper respiratory tract infections and skin infections and for wound healing activities. The work seeks to investigate the antitubercular activities of chloroformic C. asiaticum bulb extracts (CCAE) in aerosol-induced TB in a mice model using Mycobacterium smegmatis strains. From the results obtained, the histology of the infected lungs managed with 500 and 1,000 mg/kg doses of CCAE showed improved lung alveolar space, lung parenchyma, and bronchial functions. CCAE reduced significantly (p ? 0.05) the colony-forming unit/ml count of M. smegmatis on the lungs. In the assessment of tumor necrosis factor-alpha and interleukin-6 levels expressed, CCAE showed a significant (p ? 0.05) reduction in their levels. There were dose-dependent increases in red blood cells and hemoglobin, while there was a decrease in white blood cells count in the hematological analysis of CCAE treated groups compared with the negative control group. Overall, C. asiaticum bulb extract showed a promising antitubercular effect, which makes it a potential lead in the discovery and development of anti-TB agents that could help resolve issues of resistance in the management of TB.
Keywords: Interleukin-6, tumor necrosis factor-alpha, tuberculosis, multidrug-resistant, extensively drug-resistant, Crinum asiaticum